Analysis of Factors Affecting Labor Absorption in the Agricultural Sector in West Nusa Tenggara Province - Hustin, Yunia Yunara; Irwan, M; Wijimulawiani, Baiq Saripta (Westscience Press, 2024)
This study aims to analyze what factors are most dominant in influencing the absorption of labor in the agricultural sector in West Nusa Tenggara province. The variables studied include inflation, gross regional domestic product, and provincial minimum wage. The research method used is multiple linear regression analysis with data collected through library methods and documentation techniques. The results show that inflation has a positive but insignificant effect, gross regional domestic product has a negative and insignificant effect, while the provincial minimum wage has a positive and significant effect on labor absorption in the agricultural sector in West Nusa Tenggara province. The value of the determination coefficient (R²) of 0.393 shows that 39.3% of the variability of labor absorption can be explained by the three independent variables. The study concludes that the increase in inflation and the provincial minimum wage can increase labor absorption, while the increase in gross regional domestic product tends to reduce labor absorption in the agricultural sector in West Nusa Tenggara Province.